The Role of Regulatory Technology & Bankers to Prevent Money Laundering in Bank - Veranto Kurniawan (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
Bank is a financial institution that is most often used as a place for money laundering, as well as the most financial institution that sends suspicious transaction reports to the Indonesian Financial Transaction Reports and Analysis Center (PPATK). This study aims to illustrate the impact of adopting regulatory technology (regtech) and the role of AML officers in the Indonesian banking sector on money laundering prevention effectiveness. The primary data for this study was collected through a survey instrument distributed to 689 AML officers in Indonesia with the expertise in anti-money laundering (AML) compliance; there were 296 respondents that filled the questionnaire with a response rate of 42.9%. The results of multivariate analysis indicate that electronic know your customer (KYC) is not significant in money laundering prevention. Transactions monitoring (TM) of regtech and cost & time (CT) of regtech, drive money laundering prevention to a highly statistically positive & significant. Furthermore, there is a positive & significant relationship between bankers competency & awareness in money laundering prevention. Research related to regtech and AML officers in Indonesian banking sector money laundering prevention efforts is still very limited in Indonesia. This study contributes to the existing literature on anti-money laundering and the development of anti-money laundering technology.